Chromosome Interior Observation by Focused Ion Beam/Scanning Electron Microscopy (FIB/SEM) Using Ionic Liquid Technique. (10th July 2014) - Hamano, Tohru; Dwiranti, Astari; Kaneyoshi, Kohei; Fukuda, Shota; Kometani, Reo; Nakao, Masayuki; Takata, Hideaki; Uchiyama, Susumu; Ohmido, Nobuko; Fukui, Kiichi
Abstract Attempts to elucidate chromosome structure have long remained elusive. Electron microscopy is useful for chromosome structure research because of its high resolution and magnification. However, biological samples such as chromosomes need to be subjected to various preparation steps, including dehydration, drying, and metal/carbon coating, which may induce shrinkage and artifacts. The ionic liquid technique has recently been developed and it enables sample preparation without dehydration, drying, or coating, providing a sample that is closer to the native condition. Concurrently, focused ion beam/scanning electron microscopy (FIB/SEM) has been developed, allowing the investigation and direct analysis of chromosome interiors. In this study, we investigated chromosome interiors by FIB/SEM using plant and human chromosomes prepared by the ionic liquid technique. As a result, two types of chromosomes, with and without cavities, were visualized, both for barley and human chromosomes prepared by critical point drying. However, chromosome interiors were revealed only as a solid structure, lacking cavities, when prepared by the ionic liquid technique. Our results suggest that the existence and size of cavities depend on the preparation procedures. We conclude that combination of the ionic liquid technique and FIB/SEM is a powerful tool for chromosome study.